(untitled) (International Journal of Environmental Sciences, 2025)
Hypertension is one of the commonest medical complication during pregnancy.1 Despite so much research, Pre-eclampsia is one of the leading cause of maternal morbidity and mortality in India and worldwide. Incidence is 5-15% in pregnancy. High blood pressure is a sign, not a disease. About 5-15% of the pregnancy are affected by hypertensive disorder and pre-eclampsia, of which pre-eclampsia constitute of about 70% and chronic hypertension of about 30%. Its incidence in primi gravida is about 10-15% and in multi gravida is 5%.2